Networks in the Russian market economy - Markku Lonkila (Palgrave Macmillan, 2010)
If Russia has become a market economy, how does it function on a grassroots level? In addition to market mechanisms, what kinds of social and moral principles are at work in the new Russian economy? Is the 'Soviet legacy' still present in post-Soviet business practices? This book searches for answers to these questions, by investigating the networking practices of the Russian software industry. It examines what kinds of resources are transmitted through the personal networks of Russian IT directors and managers, and which mechanisms govern this transmission. The volume opens a rarely available grassroots-level view into the business practices of the new Russian knowledge-based economy. This book is essential reading for all interested in Russian society, culture and economy.
Keywords: 330; Russia; Market economy; Business practices; IT industry; Unternehmensnetzwerk; Soziale Norm; Soziales Netzwerk; Softwareindustrie; Russland